How Brand Community Practices Create Value: Evidence from Maternal Disaster - Irdan Fattur Mi'raj; Abdullah Muhammad Feisal; Erna Maulina (Entrepreneurship Faculty, Universitas Garut, 2025)
This study examines how brand community practices create value within Maternal Disaster, an independent Indonesian fashion brand rooted in underground music and subcultural aesthetics. Drawing on the theoretical framework of value-creating practices (Schau, Muñiz, & Arnould, 2009), this research employs a qualitative case study approach based on secondary data collected from digital sources, including social media content, online publications, and event documentation. The analysis identifies three key community practices, social networking, community engagement, and impression management, that collectively sustain the brand’s cultural vitality. These practices enable consumers to co-create symbolic, social, and emotional value through shared creativity, collaboration, and expressive participation. The findings reveal that Maternal Disaster functions as more than a commercial entity, it operates as a living cultural community where meaning and identity are collectively produced. Symbolic value emerges from the shared construction of artistic and ideological meanings, social value from collaborative participation and belonging, and emotional value from affective bonds among members. These interwoven dimensions generate outcomes such as strong brand attachment, voluntary advocacy, and the accumulation of cultural capital. The study contributes to the literature on brand community and co-creation by illustrating how independent brands in emerging markets can leverage cultural participation to build authenticity and resilience. Practically, it highlights that fostering organic, participatory communities can serve as a sustainable strategy for cultural and commercial differentiation in the contemporary creative economy.